Wire rod, preparation method of wire rod, mining 2400MPa-grade steel strand and manufacturing method and application of mining 2400MPa-grade steel strand
By developing high carbon and silicon element content strips for preparation of 2400MPa grade steel strands for mining, the problem of ordinary anchor cables being easily broken in impact ground pressing tunnels is solved, and anchor cables with high tensile strength and elongation are achieved, which simplifies construction and reduces costs.
Patent Information
- Application Number
- CN202411958469.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
In impact ground pressing tunnels, ordinary anchor cables are prone to breaking failure. The main reason is that their bearing capacity and elongation are low, especially under dynamic loads, which leads to mismatch with geological conditions and affects the support effect of the tunnel.
A strip was developed with a high carbon element and silicon element content and a strength of 1510MPa-1650MPa for the preparation of 2400MPa grade steel strands for mining. The strips improve the sonitization rate and tensile strength through specific chemical composition and process treatment.
The high tensile strength and elongation of the anchor cable are achieved, which meets the support and bearing capacity requirements, and simplifies the construction process, reduces costs and improves construction efficiency.
Smart Images

Figure CN119753505A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of rock burst prevention and control in tunnels, and in particular to a wire rod and a preparation method thereof, a 2400MPa grade steel strand for mining and a manufacturing method and application thereof. Background Art
[0002] In recent years, with the continuous exploitation of mining resources, more coal mines have entered the deep mining stage, and the proportion of complex and difficult tunnels such as soft, broken, and high-stress tunnels has continued to increase. When anchor cables (steel strands) are used for support in these impact ground pressure tunnels and deep soft rock tunnels, the anchor cables are prone to breakage and failure. The main reason is that ordinary anchor cables have low bearing capacity and elongation, especially the instantaneous elongation under dynamic load is low. When the anchor cable is subjected to large deformation of soft rock or impact ground pressure, the energy absorption capacity and elongation performance of the anchor cable do not match the underground geological conditions, and the anchor cable will break and fail, thereby affecting the tunnel anchor cable support effect.
[0003] The deformation of tunnels and the breakage of anchor cables in deep mining areas mainly have the following characteristics:
[0004] (1) The tunnel burial depth in the anchor cable breaking area is usually deep, generally exceeding 600m. In the deep tunnel, the tunnel support system has been subjected to high static loads without the influence of dynamic loads, and the tunnel has undergone strong deformation locally. At the same time, since the fracture of the thick and hard rock layer above the coal seam will generate high-energy dynamic loads, the tunnel support system is prone to damage and failure under high dynamic and static loads.
[0005] (2) Anchor cables are more likely to break in dynamic pressure tunnels. The tunnels are buried deep and are subject to high mining stress. Under high mining stress, anchor cables are prone to a large number of breakage failures. During tunnel excavation, the number of anchor cable breakages is relatively small, and anchor cable breakages mainly occur during mining near the working face and the working face.
[0006] (3) Generally, the lower the strength of the coal seam or rock formation, the easier it is for the anchor cable to break. Due to the low strength of the coal and rock mass, large deformation often occurs under high stress. Under the large deformation of the tunnel, a large number of ordinary high-strength anchor cables have broken.
[0007] In order to solve the problem of breaking of ordinary diameter SKP21.8-1×19 / 1860MPa anchor cables, many mining areas in my country have gradually begun to use SKP28.6-1×19 / 1770MPa (diameter 28.6mm, 1×19 strands, strength 1770MPa) anchor cables, with a breaking load of 900kN. There is no breakage during use in deep mines, but there are the following problems with large diameter anchor cables during use:
[0008] (1) High cost of anchor cable support materials. The cost of SKP28.6-1×19 / 1770MPa anchor cables is 2-3 times higher than that of ordinary SKP21.8-1×19 / 1860MPa anchor cables. The high cost of support materials has affected the large-scale promotion of SKP28.6-1×19 / 1770MPa anchor cables.
[0009] (2) The anchor cable has a large diameter, and the matching drill bits, boreholes, and anchoring agents are different, making on-site construction operations complicated. The traditional SKP21.8-1×19 / 1860MPa-grade anchor cable has a borehole diameter of 30mm, and the used anchoring agent has a diameter of 23mm. The SKP28.6-1×19 / 1770MPa-grade anchor cable has a borehole diameter of 50mm, and the used anchoring agent has a diameter of 35mm. The on-site anchor rod diameter is 22mm, while the anchor cable diameter is 28.6mm. The drill bits, borehole diameters, and anchoring agent types of the two support materials are all different. Different drill bits, anchoring agents, and other materials must be matched during the excavation process. The construction process is complicated, which greatly affects the construction efficiency.
[0010] (3) The labor intensity of workers is high, the prestressing force is low, and the support effect is not significantly improved. Since the SKP28.6-1×19 / 1770MPa anchor cable is thicker and heavier, the matching jack is also heavier, and the labor intensity of workers on site is high. At the same time, since the maximum tensioning load of the tensioning equipment used on site is 300kN, the strength of the anchor cable is significantly improved, but the prestressing force of the anchor cable is not increased, which also affects the support effect of the large-diameter anchor cable.
[0011] Ordinary SKP21.8-1×19 / 1860MPa anchor cables used in deep mines are prone to breakage, while SKP28.6-1×19 / 1770MPa anchor cables have the above-mentioned problems. It is urgent to develop an anchor cable and supporting lock that can maintain the diameter of the existing conventional anchor cable, but improve its tensile strength, fully meet the support bearing capacity requirements, and facilitate construction, improve construction efficiency, and have low cost.
[0012] In addition, the improvement of the tensile strength of the anchor cable is closely related to the raw materials used in its preparation.
[0013] Therefore, it is also necessary to develop raw materials with higher strength for the preparation of anchor cables. Summary of the invention
[0014] In view of this, an object of the present application is to provide a wire rod having a high carbon and silicon content and a strength of 1510MPa-1650MPa, which can be used for the preparation of 2400MPa grade steel strands for mining.
[0015] Another object of the present application is to provide a method for preparing wire rod.
[0016] Another object of the present application is to provide a 2400MPa grade steel strand for mining.
[0017] Another object of the present application is to provide a method for manufacturing a 2400 MPa grade steel strand for mining.
[0018] Another object of the present application is to provide a mining anchor cable.
[0019] To achieve the above object, the first aspect of the present application provides a wire rod, characterized in that the chemical composition of the wire rod is as follows by mass percentage:
[0020] C: 0.92-0.97%, Si: 1.00-1.10%, Mn: 0.50-0.60%, P≤0.015%, S≤0.015%, Cu≤0.10%, Ni≤0.015%, Cr≤0.40%, V≤0.1%, and the balance is Fe.
[0021] The wire rod described in the present application has a high content of carbon and silicon elements and a strength of 1510-1650 MPa, and can be used for the preparation of 2400 MPa grade steel strands for mining.
[0022] In some embodiments, the metallographic structure of the wire rod is troostite, and the troostitization rate is above 95%.
[0023] In some embodiments, the diameter of the wire rod includes 14.0 mm and 8.0 mm, and the allowable deviation range is ±0.20 mm, and the ovality is less than 0.15 mm.
[0024] In some embodiments, the wire rod has an initial strength of 1510-1650 MPa and a cross-sectional shrinkage of more than 30%.
[0025] In some embodiments, the coil diameter of each coil of the wire rod is 1.35-1.4 m.
[0026] The second aspect of the present application provides a method for preparing a wire rod, comprising:
[0027] Design the chemical composition of ingredients;
[0028] The ingredients are subjected to converter, LF refining, RH vacuum degassing, and then rolled into shape by two-fire forming to obtain the wire rod body;
[0029] The wire rod body is subjected to austenitizing heating and isothermal salt bath sorbitizing treatment to obtain the wire rod.
[0030] The preparation method of the wire rod described in the present application adopts a chemical composition of high C and high Si, and adopts the process of "austenitizing heating + isothermal salt bath troostitizing treatment". The wire rod body quickly enters the salt bath tank for isothermal troostitizing phase transformation in a fine and uniform austenite structure state, and the salt bath temperature is precisely and stably controlled. The obtained troostite structure pellets are fine and uniform, the interlamellar spacing is small, and the troostitizing rate is high (which can be increased from 85% of ordinary wire rod to more than 95%). While achieving high strength (more than 1510MPa), it solves the problem of poor plastic toughness indicators of the wire rod after high C and high Si strengthening treatment, which causes broken wire in the subsequent wire drawing process and prevents normal production.
[0031] In some embodiments, the chemical composition of the ingredients is calculated by mass percentage: C: 0.92-0.97%, Si: 1.00-1.10%, Mn: 0.50-0.60%, P≤0.015%, S≤0.015%, Cu≤0.10%, Ni≤0.015%, Cr≤0.40%, V≤0.1%, and the balance is Fe.
[0032] In some embodiments, the rolling is performed by the Morgan seventh generation 8+4 rolling mill. The sizing unit of the Morgan seventh generation 8+4 rolling mill can realize single pass rolling and free specification rolling. The same finishing pass system can roll a wide range of arbitrary specifications and high-precision products by adjusting the roll gap.
[0033] In some embodiments, during the rolling process, a φ250 mm round billet is used to roll a φ14.0 mm wire rod body, and the compression ratio is 318.9%. The φ250 mm round billet is used to roll a φ14.0 mm wire rod, and the compression ratio is 318.9%. Compared with the φ150 mm round billet used to roll a φ14.0 mm wire rod, the compression ratio is increased by 177.8%. The high compression ratio rolling process effectively reduces the effects of defects such as central segregation and central porosity inside the ingot, and the grains are significantly refined, meeting the design requirement that the wire rod grain size (pearlite cluster) is not less than level 7.
[0034] The third aspect of the present application provides a 2400 MPa grade steel strand for mining, which is manufactured using the wire rod described in the present application or the wire rod prepared by the method for preparing the wire rod described in the present application as raw material.
[0035] The mining-use 2400MPa grade steel strand described in the present application is manufactured using the wire rod described in the present application or the wire rod prepared by the wire rod preparation method described in the present application as raw material, and can obtain higher tensile strength.
[0036] In some embodiments, the diameter of the 2400 MPa grade steel strand for mining is 21.8 mm.
[0037] In some embodiments, the 2400 MPa grade steel strand for mining has a Westrule structure.
[0038] In some embodiments, the tensile strength of the 2400 MPa grade steel strand for mining is 2400-2600 MPa, the elongation is greater than 6%, and the maximum force is 750-814 kN.
[0039] The fourth aspect of the present application provides a method for manufacturing a 2400 MPa grade steel strand for mining, comprising:
[0040] The wire rod is subjected to a surface treatment of pickling and phosphating to obtain a surface-treated wire rod;
[0041] The surface treated wire rod is subjected to wire drawing, twisting, stabilization treatment and layer winding to obtain the mining-use 2400MPa grade steel strand.
[0042] In some embodiments, the method for manufacturing the 2400 MPa grade steel strand for mining further includes the step of designing the structure of the steel strand to be a Westrule structure.
[0043] In some embodiments, the surface treatment includes wire rod threading, submersible washing, at least one pickling, immersion, first rinsing, first warm washing, phosphating, second rinsing, second warm washing, saponification, drying and wire rod offline.
[0044] In some embodiments, the submersible pool used for the submersible washing is provided with an oil heating system for preheating the submersible pool.
[0045] In some embodiments, the pickling, leaching and phosphating are all carried out under conditions of intermittent air blowing and stirring.
[0046] In some embodiments, the pickling is performed five times, and the concentration of the acid used in each pickling is 5-14wt%, 10-20wt%, 12-20wt%, 14-21wt%, and 14-21wt% respectively from the beginning to the end of the pickling.
[0047] In some embodiments, the total time of the pickling is 18-22 minutes.
[0048] In some embodiments, the immersion time is 12-15 seconds.
[0049] In some embodiments, the first flushing and the second flushing are both performed for 1-2 minutes.
[0050] In some embodiments, the total acidity of the phosphating is 85-105, the free acidity is 12-15, the acid ratio is 5-8, and the phosphating time is 4-6 min.
[0051] In some embodiments, during the wire drawing process, both the outer layer wire semi-finished product and the inner layer wire semi-finished product are drawn in 9 passes, the working cone angles of the first two dies are 11-12°, the working cone angles of the last two dies are 7-8°, and the sizing zone is 0.2d.
[0052] In some embodiments, during the wire drawing process, the outer layer wire semi-finished product is drawn from 14.0 mm to 5.55 mm, and the compression rate is 84.28%.
[0053] In some embodiments, during the wire drawing process, the inner layer wire semi-finished product is drawn from 8 mm to 3.15 mm, with a compression rate of 84.49%.
[0054] In some embodiments, during the wire drawing process, the center wire semi-finished product is drawn from 14.0 mm to 6.25 mm, with a compression rate of 80.07%, and an 8-pass drawing process is adopted.
[0055] In some embodiments, the wire drawing speed is set below 3 m / s.
[0056] In some embodiments, the allowable deviations of the diameters of the outer layer wire semi-finished product, the inner layer wire semi-finished product, and the center wire semi-finished product are all -0.01 mm to +0.02 mm.
[0057] In some embodiments, the twisting pitch setting value is 10-16 times the nominal diameter of the 1×19S-Φ21.8mm steel strand.
[0058] In some embodiments, during the stabilization treatment, the tension is 310-330 kN, the tempering temperature is 380-400°C, the vehicle speed is 38-42 m / min, and the cooling water temperature is 25-60°C.
[0059] The manufacturing method of the 2400MPa grade steel strand for mining described in this application can at least bring the following beneficial effects:
[0060] (1) The wire rod described in the present application is used as raw material. Since the wire rod adopts a scientific and reasonable strengthening high C and high Si chemical composition and adopts an isothermal molten fluid heat treatment process, the average initial strength of the Φ14.00 mm wire rod reaches more than 1620 MPa, and the initial strength of the Φ8.00 mm wire rod reaches more than 1572 MPa. Therefore, the steel strand manufactured using the wire rod as raw material has an ultra-high tensile strength (more than 2400 MPa).
[0061] (2) The wire rod surface treatment process adopts the pickling and phosphating surface treatment production line. Compared with the non-pickling phosphating process currently used in the market, this process produces a more uniform, firm and durable phosphating film. Among them, the pre-heating of the submersible washing ensures that the bath liquid can reach the process requirements of normal temperature in winter, which helps the reaction of hydrochloric acid and iron oxide to thoroughly clean the iron oxide, creating conditions for obtaining a uniform and firm phosphating film in the future.
[0062] (3) The phosphating process was optimized, with a total acidity (point): 85-105, free acidity (point): 12-15; acid ratio: 5-8, phosphating time: 4-6min, which is different from the ordinary production process. Through the optimization of the medium-temperature zinc phosphating treatment process and the extension of the phosphating time, the thickness of the phosphating film after treatment reached 9.0-10.2g / m 2 (The thickness of the conventional product phosphate film is 6.0-7.0g / m 2 ), and the phosphating film is uniform and dense, and can withstand temperatures of 400 to 500°C, which effectively solves the wear of the die during ultra-high strength wire rod drawing, improves the surface quality of the steel wire, and is also beneficial to the improvement of the corrosion resistance and stress corrosion resistance of the finished steel strand.
[0063] (4) Through the structural design of steel strands, the formulation of reasonable wire drawing, twisting and stabilization treatment processes can improve the comprehensive performance of 2400MPa grade steel strands for mining. Specifically:
[0064] 1) Through the structural design of the steel strand, the outer wire, inner wire and center wire are optimally matched in size. The gap between the three layers of steel wire is 0.10-0.30mm. With the small twist length design, after the stabilization process, the stress state between each layer of steel wire is balanced. The obtained ultra-high strength steel strand has a compact structure, is not loose, and does not draw wires, which effectively solves the problems of loose strands and drawing wires that are easy to occur in ultra-high strength steel strands.
[0065] 2) A small-angle working cone and a short sizing belt design are used to avoid heat accumulation caused by an excessively long sizing belt; the small-angle working cone design helps the drawing powder lubricant to form a dense and uniform lubricating film on the surface of the steel wire, improving the surface quality while also making up for the short service life of the die caused by the shortening of the sizing belt. According to the 9-pass deformation design, the working cones of the first two dies are designed to be 11°~12°; the working cone angles of the last two dies are designed to be 7°~8°, and the sizing belt is controlled at 0.2d. The drawing production is monitored, and the die consumption can reach about 0.09 pieces / ton, which is the same as the ordinary die consumption.
[0066] 3) Improved drawing process. The outer wire semi-finished product was drawn from 14.0mm to 5.55mm, with a compression rate of 84.28%, using a 9-pass drawing process; the inner wire semi-finished product was drawn from 8mm to 3.15mm, with a compression rate of 84.49%, using a 9-pass drawing process; the center wire semi-finished product was drawn from 14.0mm to 6.25mm, with a compression rate of 80.07%, using an 8-pass drawing process. This improvement is consistent with the motor power of the tank of each pass of the wire drawing machine, and reasonably distributes the compression rate of each pass, which can fully guarantee the drawing power, ensure the smooth drawing of ultra-high strength wire rods, and effectively solve the problem of wire breakage that is easy to occur during the drawing process of ultra-high strength wire rods.
[0067] 4) A small lay pitch design process is adopted, and the lay pitch is set to 10-16 times the nominal diameter of the 1×19S-Φ21.8mm steel strand. After the stabilization treatment process, the obtained ultra-high-strength steel strand has a compact structure and is not loose.
[0068] 5) Increase the process temperature of stabilization treatment to make the tempering state of steel strands sufficient, so that the atoms of carbon and other alloy elements in the organization can diffuse faster, realize the recombination of atoms, and gradually transform the unstable unbalanced organization into a stable balanced organization, eliminate the internal stress, and improve the plasticity index. Through the process cross test, the best match between the process temperature and tension of stabilization treatment was obtained, and the process plan was determined as: tension 310-330kN, tempering temperature 380-400℃, vehicle speed 38-42m / min, cooling water temperature 25-60℃ (optimal situation: tension 320kN, tempering temperature 390℃, vehicle speed 40m / min, cooling water temperature 25℃). The elongation of the steel strand produced after trial production is ≥6.5%, and the tensile strength of the steel strand reaches the design requirement of 2400MPa. The steel strand obtained in the test has a normal plastic fracture.
[0069] (5) The ultra-high-strength anchor cable (i.e., 2400MPa grade steel strand for mining) manufactured has high tensile strength and large elongation, and can effectively replace the SKP28.6-1×19 / 1770MPa (diameter 28.6mm, 1×19 strands, strength 1770MPa) grade anchor cable for mining. The ultra-high-strength anchor cable has a diameter of 21.8mm, 1×19 strands, a tensile strength greater than 2400MPa, an elongation greater than 6%, and a maximum force greater than 750kN.
[0070] (6) The ultra-high-strength anchor cable (i.e., 2400MPa grade steel strand for mining) manufactured has low cost, convenient construction and higher construction efficiency.
[0071] The fifth aspect of the present application provides a mining anchor cable, comprising the mining 2400 MPa grade steel strand described in the present application or the mining 2400 MPa grade steel strand manufactured by the mining 2400 MPa grade steel strand manufacturing method described in the present application.
[0072] The lock described in the present application has at least the beneficial effects of the wire rod and its preparation method, and the 2400MPa grade steel strand for mining and its manufacturing method.
[0073] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0074] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0075] in:
[0076] Figure 1 It is a process flow chart of pickling and phosphating surface treatment shown in an exemplary embodiment of the present application.
[0077] Figure 2 It is 1×19S-Φ21.8mm Westerly type structural steel strand and matching wire size.
[0078] Figure 3 This is a photo of the steel strands being in a scattered state and cannot be restored by hand.
[0079] Figure 4 The following are photos comparing the looseness of steel strands at different lay lengths.
[0080] Figure 5 This is a metallographic photograph of the Φ14.00 mm wire rod obtained by isothermal salt bath sorbitization treatment in Example 1.
[0081] Figure 6 This is a metallographic structure photograph of the wire rod of comparative example 1 with a diameter of 14.00 mm that was not subjected to isothermal salt bath sorbitization treatment.
[0082] Figure 7 This is a photograph of the normal plastic fracture of the Φ5.55 outer layer wire semi-finished product in Example 1.
[0083] Figure 8 This is a photo of the good plastic fracture (i.e., normal steel wire fracture) of the 1×19S-Φ21.8mm steel strand after the tensile test in Example 1.
[0084] Fig. 9 Schematic diagram of mining anchor cable.
[0085] Fig.10 This is a photo of a 200-ton tensile testing machine.
[0086] Fig.11 This is a photo of the anomaly that occurred during the tensile test.
[0087] Fig.12 This is a photo of the normal plastic fracture successfully obtained in the improved steel strand test.
[0088] Reference numerals:
[0089] 1-Steel strand; 2-Mine anchor cable; 3-Support plate; 4-Outer wire; 5-Inner wire; 6-Center wire. DETAILED DESCRIPTION
[0090] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0091] In this application, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.
[0092] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0093] The following describes the wire rod, the method for preparing the wire rod, the 2400MPa grade steel strand for mining and the method for manufacturing the wire rod of the embodiments of the present application with reference to the accompanying drawings, wherein the wire rod and the method for preparing the wire rod are described as a part of the method for manufacturing the 2400MPa grade steel strand for mining, and they can also exist independently of the method for manufacturing the 2400MPa grade steel strand for mining as the wire rod and the method for preparing the wire rod, so as to illustrate and support the wire rod and the method for preparing the wire rod of the present application.
[0094] The manufacturing method of the mining 2400MPa grade steel strand in the embodiment of the present application has the following production process:
[0095] Wire rod development → inspection and testing → pickling and phosphating surface treatment → inspection → drawing (also known as wire drawing) → semi-finished product inspection and testing → stranding (also known as twisting) → stabilization treatment → layer winding → finished product inspection and testing → packaging → warehousing.
[0096] 1. Development of wire rod (also known as preparation of wire rod)
[0097] 1. Design of initial strength of raw materials
[0098] Designed according to the tensile strength calculation formula (1):
[0099]
[0100] In formula (1): R n - Tensile strength of steel wire after drawing (MPa);
[0101] k - strengthening coefficient related to drawing conditions (lubrication, cooling);
[0102] R0 - original tensile strength of wire rod (MPa);
[0103] d0 - diameter of wire rod before drawing (mm);
[0104] d n - Diameter of the wire after drawing (mm).
[0105] Combined with the characteristics of wire drawing equipment, the strengthening coefficient k is determined to be in the range of 0.98-1.03. The design uses Ф8.0mm wire rod to produce Ф3.15mm semi-finished steel wire. The tensile strength of Ф3.15mm semi-finished steel wire must reach more than 2400MPa. After calculation, the initial strength of the Ф8.0mm wire rod used must reach more than 1510MPa. The raw materials used to produce Ф6.25mm and Ф5.55mm semi-finished steel wires are designed according to the Ф14.0mm specification, and their initial strength must also reach more than 1510MPa. Considering the strength loss during the stabilization process and the increase in insurance value for the finished steel strand, the initial strength of the wire rod is determined to be 1510MPa-1650MPa.
[0106] 2. Raw material composition design
[0107] The inventors found that with the development and production of ultra-high-strength steel strands, the design and development of domestic ultra-high-strength wire rods have been driven, and the level of source material preparation has been improved. The development of ultra-high-strength wire rods has also undergone different process steps. Initially, a single strengthening element C and Mn was used to produce wire rods for ultra-high-strength steel strands. The maximum tensile strength could reach about 1300MPa, which could not meet the initial strength requirements of wire rods for ultra-high-strength steel strands. In addition, simply increasing the C content would reduce the plastic toughness index of the raw wire rod, which would cause wire breakage in the subsequent drawing process, low yield rate and low elongation of the steel strand.
[0108] After innovative development, some domestic raw material manufacturers have improved the initial strength of wire rods by micro-alloying the chemical composition of wire rods and improving processes such as controlled rolling and controlled cooling. The initial strength of the Ф14-16mm hot-rolled wire rods produced has reached the range of 1400-1470MPa, meeting the development needs of 2160MPa ultra-high-strength steel strands. However, the initial strength of the wire rods above 1500MPa designed for the product in this application is still not met.
[0109] Therefore, the inventors studied the chemical composition (ie ingredients) of the raw wire rod and found that the raw material with high C and high Si chemical composition can meet the initial strength requirement of the wire rod above 1510 MPa.
[0110] In some embodiments, the main chemical components of the raw wire rod are as shown in Table 1.
[0111] Table 1 Main chemical components of raw wire rod (ingredients)
[0112] C, wt% Si, wt% Mn, wt% P, wt% S, wt% Cu, wt% Ni, wt% Cr, wt% V, wt% 0.92-0.97 1.00-1.10 0.50-0.60 ≤0.015 ≤0.015 ≤0.10 ≤0.015 ≤0.40 ≤0.1%
[0113] As an optional example, the chemical composition of the raw wire rod (i.e., ingredient) is calculated by mass percentage as follows: C: 0.92-0.97%, Si: 1.00-1.10%, Mn: 0.50-0.60%, P≤0.015%, S≤0.015%, Cu≤0.10%, Ni≤0.015%, Cr≤0.40%, V≤0.1%, and the balance is Fe.
[0114] It should be noted that the chemical composition of the raw wire rod (also known as the ingredient) is used to test the composition of the molten steel in steelmaking. The range determined by this composition will not change due to the manufacturing of subsequent processes, that is, its chemical composition does not change from steelmaking to the forming of the wire rod into the final product.
[0115] The inventors further discovered that although the chemical composition of the raw wire rod with high C and high Si content improves the initial strength of the wire rod to above 1510 MPa, after the C content is increased, the wire rod is prone to central segregation and the appearance of structural defects such as martensite and network cementite, making it impossible to obtain a suitable drawing structure. Therefore, the step of isothermal molten fluid heat treatment of the wire rod is added.
[0116] In some embodiments, the method for preparing the wire rod further comprises the following steps:
[0117] The ingredients (i.e., the chemical composition shown in Table 1) are refined in a converter and LF, subjected to RH vacuum degassing, and then rolled into a wire rod body through two-fire forming.
[0118] The wire rod body is subjected to austenitizing heating and isothermal salt bath sorbitizing treatment to obtain the wire rod.
[0119] In some embodiments, the rolling is performed by the seventh generation 8+4 rolling mill of MORGAN. The sizing unit of the seventh generation 8+4 rolling mill of MORGAN can realize single pass rolling and free specification rolling. The same finishing pass system can roll a wide range of arbitrary specifications and high-precision products by adjusting the roll gap.
[0120] It should be noted that the above ingredients are refined in a converter and LF, and then RH vacuum degassed, and then rolled into shape by two-fire. Two-fire rolling is the rolling of steel by heating twice. During this period, the processes of peeling and grinding the billet are added, and the billet is re-opened to make the structure more uniform. Through two heating rolling, defects such as pores and inclusions in the wire rod can be better eliminated, the tensile properties and ductility of the wire rod can be improved, and the risk of fracture can be reduced. The rest are well known technologies in the field and will not be repeated here.
[0121] Exemplarily, the method of austenitizing heating is: an offline salt bath process is adopted, in which the wire rod is re-laid out, and the wire rod in a round state is straightened and then enters a heating furnace for austenitizing heating. The austenitizing heating temperature is 900°C to 960°C. After keeping warm for 10 minutes, it is quickly transferred to a cooling salt bath furnace.
[0122] Exemplarily, the method of isothermal salt bath troostitizing treatment is: implement 500℃ salt bath isothermal heat treatment. The wire rod quickly enters the salt bath tank for isothermal troostite phase transformation in a fine and uniform austenite structure state. Since the salt bath temperature is precisely controlled and has small fluctuations, it can ensure that the obtained troostite structure pellets are fine and uniform, the interlamellar spacing is small, and the troostitization rate is high, ultimately achieving the purpose of simultaneously improving the strength, plasticity, and toughness of the wire rod. Exemplarily, the salt bath uses a nitrite mixed salt in a molten state, and the single wire salt bath treatment time is 2-3min.
[0123] Offline salt bath is to straighten the wire rod and then perform austenitization heating and isothermal salt bath sorbite phase transformation. Compared with the online salt bath, the wire rod comes out of the finishing mill and is formed into a coiled circle by the spinning machine and enters the salt bath tank. There is overlap between the coiled circles of the wire rod, and the overlapping parts are prone to problems such as uneven wire rod transformation. Offline salt bath is a heat treatment for a single wire rod. The treatment process is more uniform, more conducive to the phase transformation process, and a fine, uniform and good sorbite structure can be obtained.
[0124] In the embodiments of the present application, the ingredients are refined in a converter and LF, and then RH vacuum degassed, and then rolled into shape by two fires. The wire is then heated by a controlled atmosphere heating furnace, and the "austenitization heating + isothermal salt bath troostitization treatment" process is adopted. The wire rod quickly enters the salt bath tank for isothermal troostite phase transformation in a fine and uniform austenite structure state. The salt bath temperature is precisely and stably controlled, and the obtained troostite structure pellets are fine and uniform, with small interlamellar spacing and a high troostitization rate. After this technical solution, the troostitization rate of the obtained wire rod can be increased from 85% of ordinary wire rod to more than 95%, achieving high strength while making the wire rod have excellent mechanical properties, solving the problem of poor plastic toughness index of the wire rod after high C and high Si strengthening treatment, resulting in broken wires in the subsequent wire drawing process and unable to produce normally.
[0125] In some embodiments, the chemical composition of the wire rod is, by mass percentage, C: 0.92-0.97%, Si: 1.00-1.10%, Mn: 0.50-0.60%, P≤0.015%, S≤0.015%, Cu≤0.10%, Ni≤0.015%, Cr≤0.40%, V≤0.1%, and the balance is Fe.
[0126] It should be noted that the chemical composition of the wire rod is the chemical composition of the wire rod obtained by subjecting the wire rod body to austenitizing heating and isothermal salt bath sorbitizing treatment.
[0127] In some embodiments, the wire rod diameters designed according to the semi-finished wire size include: Ф14.0mm and Ф8.0mm, which are used to produce Ф6.25mm, Ф5.55mm and Ф3.15mm semi-finished steel wires, respectively.
[0128] In some embodiments, the diameter of the wire rod is designed to be allowed to be within ±0.20 mm, and the ovality is ≤0.15 mm, which is stricter than the dimensional control level of ordinary wire rods (the diameter allowable deviation is ±0.30 mm, and the ovality is ≤0.48 mm). This is mainly based on the following considerations: The initial strength of the wire rod used in the 2400MPa grade steel strand product for mining in this application is designed to reach more than 1510MPa, and the strength is high while the surface hardness is increased. The influence of uneven deformation of the wire rod should be reduced, thereby reducing the increase in drawing stress caused by the increase in deformation, and reducing the low yield rate or inability to use normally caused by surface quality defects such as drawing cracks or drawing fractures.
[0129] 2. Pickling and phosphating surface treatment
[0130] In the embodiments of the present application, by performing pickling and phosphating surface treatment on the wire rod obtained in step one, a more uniform, firm and durable phosphating film can be obtained compared to the existing non-pickling phosphating treatment process.
[0131] Figure 1 FIG. 1 is a process flow chart of pickling and phosphating surface treatment according to an exemplary embodiment of the present application. Figure 1 As shown, in the embodiment of the present application, the pickling and phosphating surface treatment includes wire rod threading, diving washing, at least one of the pickling, immersion, first rinsing, first warm washing, phosphating, second rinsing, second warm washing, saponification, drying and wire rod offline.
[0132] in:
[0133] Wire rod threading refers to that the ground loading vehicle delivers the used raw material wire rod to the hanging moving device. Exemplarily, the hanging moving device includes a crane and the like.
[0134] The method of submersible washing is: put the raw material wire rod into a submersible pool filled with water for soaking. Specifically, it can be: the hanging moving device runs on the track. The various process tanks are distributed in a reasonable position below the track. The entire operation is a program-controlled closed cycle. The hanging moving device loaded with the raw material wire rod can complete the processing of each process. The first thing to enter is the submersible pool. The submersible pool can be filled with water in advance and the raw material wire rod is placed in the pool to avoid the equipment hatch directly opening the line to meet environmental protection requirements. At the same time, the submersible pool has heating coils, etc., which can preheat the raw material wire rod in winter to ensure the process temperature and ensure that the hydrochloric acid can fully react with the oxidized iron sheet.
[0135] The pickling method is: soak the raw wire rod that has been washed by submersible in acid. Specifically, the soaking can be carried out in an acid tank, which has six acid tanks, five of which are working acid tanks and one is a spare acid tank. The new acid tank is filled or replenished with new acid, which is directly added from the new acid tank to meet the process concentration requirements. Exemplarily, the new acid includes hydrochloric acid and other acid solutions, which dissolve the oxides on the surface of the wire rod through hydrochloric acid and other acids, and thoroughly remove the oxides and rust stains on the surface of the wire rod after pickling.
[0136] Immersing means washing the acid such as the hydrochloric acid on the surface of the pickled raw wire rod with water.
[0137] The first flushing method is: the first flushing is to flush the residue of the previous hydrochloric acid solution to prevent the acid solution from being brought into the phosphating tank, improve the wire rod pickling quality and ensure the subsequent phosphating quality. The first flushing uses a high-pressure water gun with a pressure of 0.4-0.5MPa and a 15kW centrifugal pump.
[0138] The first warm washing method is: use 25-50°C hot water to wash the raw wire rod after the first washing. The first warm washing is to increase the temperature of the raw wire rod after the first washing, which is beneficial to ensure the subsequent phosphating process temperature and improve the phosphating quality.
[0139] The second flushing method is to rinse the phosphating liquid remaining on the surface and gaps of the wire rod to prevent the residual phosphoric acid from being brought into the saponification tank. The second flushing uses a high-pressure water gun to flush the phosphating wire rod, with a pressure of 0.4-0.5MPa, and a 15kW centrifugal pump is used for flushing.
[0140] The second warm washing method is: use 25-50℃ hot water to wash the phosphating wire rod after the second washing. The surface temperature of the phosphating wire rod will decrease after the second washing. Re-performing the second warm washing can increase the temperature of the wire rod, which is beneficial to ensure the temperature of the saponification process.
[0141] The saponification method is: after adding saponification liquid into the saponification tank, the temperature is raised to the set process parameter range, and the lubricity of the wire rod drawing can be increased after saponification. Exemplarily, the saponification liquid uses a sodium stearate solution, the saponification temperature is 75-90°C, and the saponification time is 30s to 1min. In the embodiments of the present application, there is no requirement for the concentration of the sodium stearate solution.
[0142] Wire rod off-line means that after all processes are completed, the hanging mobile device puts the surface-treated wire rod onto the ground loading car.
[0143] The diameter of each roll of the salt bath wire rod (that is, the wire rod finally prepared in the embodiment of the present application) is 1.35-1.4m, while the diameter of the ordinary wire rod is only 1.15-1.2m. The surface treatment of the large-diameter wire rod is prone to problems such as the iron oxide scale cannot be washed cleanly and the phosphating film is not easy to adhere. The quality after surface treatment cannot provide guarantee for the drawing production of 1600MPa ultra-high strength wire rod.
[0144] Since the space of the tank is fixed, the scale of iron oxide in the gap of the large diameter wire rod is not easy to clean, and it requires more process guarantee. However, especially in winter, the ambient temperature is low, the wire rod is large, and the process temperature cannot be guaranteed, which brings difficulties to the subsequent wire drawing production. For this reason, in some cases, the embodiments of the present application independently design and add an oil heating system in the submersible pool used for submersible washing, and preheat the submersible pool to solve the problem that the process temperature of ultra-high strength wire rod washing is low and the surface quality cannot meet the requirements. Pre-heating is implemented to ensure that the tank liquid can also meet the process requirements of normal temperature in winter, which is conducive to the reaction of hydrochloric acid and scale of iron oxide, helps to thoroughly clean the scale of iron oxide, and creates conditions for obtaining a uniform and firm phosphating film in the future.
[0145] In addition, usually, the liquid level of the tank for pickling, leaching and phosphating is in a static state, but the iron oxide scale of the large diameter wire rod is not easy to be cleaned due to limited space. Therefore, in some embodiments, submersible washing, pickling, leaching and phosphating are all carried out under the condition of intermittent air blowing and stirring.
[0146] Exemplarily, an air blowing device is added to each of the pickling, immersion and phosphating tanks to keep the liquid in the tank in a flowing state, and an intermittent stirring process is designed.
[0147] It should be noted that the air blowing device can be a steam heating pipe, an air blowing and stirring solenoid valve, a steam solenoid valve, etc.
[0148] In some embodiments, the intermittent air blowing stirring may be an average air blowing of 10 seconds and an intermittent stirring of 60 seconds. This can continuously maintain the flow of the liquid surface, achieve the effect of making the concentration of the tank liquid uniform, help to thoroughly clean the iron oxide scale, improve the adhesion of the phosphating film, and create conditions for the subsequent drawing production of ultra-high strength wire rods.
[0149] In some embodiments, the pickling is performed 5 times, which are the first pickling, the second pickling, the third pickling, the fourth pickling and the fifth pickling, respectively. The concentration of the acid (e.g., hydrochloric acid) used in each pickling is 5-14wt% (first pickling), 10-20wt% (second pickling), 12-20wt% (third pickling), 14-21wt% (fourth pickling), and 14-21wt% (fifth pickling).
[0150] In the embodiments of the present application, appropriately extending the total pickling time is conducive to the full reaction of hydrochloric acid with the iron oxide scale, which helps to thoroughly clean the iron oxide scale and create conditions for subsequently obtaining a uniform and firm phosphating film.
[0151] In some embodiments, the total pickling time is controlled to be 18-22 minutes.
[0152] In some embodiments, the immersion time is 12-15 seconds.
[0153] In some embodiments, the duration of the first flush and the second flush is 1-2 min, preferably 1 min.
[0154] In the embodiment of the present application, the time for the first rinse and the second rinse is extended to 1-2 minutes compared with the normal process of 30 seconds, which can thoroughly rinse out the residual hydrochloric acid liquid of the previous process, avoid the residual hydrochloric acid on the surface of the large-diameter wire rod, ensure the surface quality of the wire rod, and also avoid rust on the surface of the wire rod caused by the residual hydrochloric acid.
[0155] In the embodiment of the present application, as the acid solution reacts on the steel substrate surface, carbon particles are precipitated on the steel substrate surface as attachment crystal nuclei, and the formed zinc iron phosphate is deposited on the crystal nuclei and grows to form a phosphating film. The chemical reaction process of phosphating is as follows.
[0156] Fe+2H + →Fe 2+ +H2↑
[0157] H3PO4→H + +H2PO4 - 、H2PO4 - →H + +HPO4 2- 、HPO4 2- →H + +PO4 3- (Level by level)
[0158] 3Zn 2+ +2PO4 3- →Zn3(PO4)2↓
[0159] 2Zn 2+ +Fe 2++2PO4 3- →Zn2Fe(PO4)2↓
[0160] The phosphating film deposition environment ultimately determines the thickness of the formed phosphating film and the density of the surface. Therefore, the medium-temperature zinc-based phosphating treatment process is optimized, and warm washing and preheating are added before phosphating to ensure the phosphating process temperature and appropriately extend the phosphating time.
[0161] In some embodiments, the phosphating method is: immersing the wire rod after the first warm wash in a phosphating solution for phosphating treatment. Exemplarily, the phosphating solution includes phosphate and zinc salt.
[0162] In some embodiments, the total acidity (point) of phosphating is 85-105, the free acidity (point) is 12-15, the acid ratio is 5-8, and the phosphating time is 4-6 min.
[0163] Exemplarily, the total acidity (point) of phosphating is 95, the free acidity (point) is 13.5, the acid ratio is 6.5, and the phosphating time is 5 minutes.
[0164] It should be noted that in the embodiments of the present application, submersible washing, multiple pickling, immersion washing, and the first rinse can all be classified as acidification processes; while the first warm wash, phosphating, second rinse, and second warm wash are classified as phosphating processes, and the saponification and drying process is the process in which the wire rod completes saponification and lubrication, and then enters the drying tank to dry the surface of the wire rod by the hot circulating air from the heater.
[0165] It should also be noted that in the embodiments of the present application, the above-mentioned pickling process and phosphating process can be operated manually or by an automated production line.
[0166] For example, the pickling and phosphating surface treatment adopts a new type of fully automatic environmentally friendly closed program-controlled pickling and phosphating surface treatment production line. The equipment adopts a closed and program-controlled form, and takes into account the online environmental protection plan, realizing a continuous automatic operation mode, greatly improving production efficiency, reducing production costs, and purifying the production environment. The ground loading vehicle delivers the wire rod to the hanging mobile device, and according to the pre-set automatic control program and process parameters, it is transported one by one to the diving pool, pickling, immersion, rinsing, phosphating, saponification layer and other process tanks for surface treatment and processing. Finally, after drying, the wire rod is offline.
[0167] In the embodiment of the present application, the thickness of the phosphating film after pickling and phosphating surface treatment reaches 9.0-10.2g / m 2 (The thickness of the conventional product phosphate film is 6.0-7.0g / m 2), and the phosphating film is uniform and dense, and can withstand temperatures of 400-500°C, which effectively solves the wear of the die during ultra-high strength wire rod drawing, improves the surface quality of the steel wire, and is also beneficial to the improvement of the corrosion resistance and stress corrosion resistance of the finished steel strand.
[0168] 3. Drawing (Wire Drawing)
[0169] (1) Improve the mold
[0170] The high initial strength of the wire rod makes the tensile strength and surface hardness of the semi-finished steel wire higher than those of ordinary conventional products. The deformation resistance of the steel wire increases during the drawing process, and the heat increases. The use of ordinary dies is prone to drawing cracks and reduces the service life of the dies. Therefore, the die used for drawing ultra-high-strength wire rods has been improved:
[0171] The design of small-angle working cone and short sizing belt is adopted to avoid heat accumulation caused by too long sizing belt; the design of small-angle working cone helps the drawing powder lubricant to form a dense and uniform lubricating film on the surface of the steel wire, improves the surface quality and also makes up for the short service life of the die caused by the shortening of the sizing belt. According to the design of 9-pass drawing deformation, the working cone of the first two dies is designed to be 11°~12°; the working cone angle of the last two dies is designed to be 7°~8°, and the sizing belt is controlled at 0.2d. The drawing production is monitored, and the consumption of the die can reach about 0.09 pieces / ton, which is the same as the consumption of ordinary dies.
[0172] (2) Control the size of semi-finished steel wire
[0173] The allowable diameter deviation of the semi-finished steel wire is controlled to (+0.02 -0.01) mm, which is stricter than the dimensional deviation requirement of ordinary steel wire. This is mainly based on the consideration of obtaining the homogeneity and compactness of the finished steel strand and creating conditions for matching with ultra-high-strength anchors.
[0174] Design drawing process:
[0175] The inner wire semi-finished product is drawn from 8mm to 3.15mm, with a compression rate of 84.49%, using a 9-pass drawing process:
[0176] 8.00→7.20→6.40→5.70→5.09→4.56→4.12→3.75→3.42→3.15
[0177] The outer layer wire semi-finished product is drawn from 14.0mm to 5.55mm, with a compression rate of 84.28%, using a 9-pass drawing process:
[0178] 14.00→12.80→11.52→10.25→9.15→8.19→7.38→6.68→6.07→5.55
[0179] The center wire semi-finished product is drawn from 14.0mm to 6.25mm, with a compression rate of 80.07%, using an 8-pass drawing process:
[0180] 14.00→12.80→11.52→10.25→9.15→8.19→7.38→6.68→6.25.
[0181] (3) Control the pulling speed
[0182] Under good lubrication conditions and cooling system, increasing the drawing speed will increase the strength of the drawn steel wire and reduce its toughness. Only by designing the most reasonable drawing speed can we obtain good plasticity and toughness indicators while ensuring strength.
[0183] The inventors compared the performance of the drawn state of the ultra-high strength wire rod and the semi-finished steel wire obtained at a speed of 3m / s and 4-4.5m / s, respectively, and obtained the following results:
[0184] The wire drawing speed is 3m / s, and the die temperature during the drawing process is controlled below 100°C. The obtained steel wire has good surface quality and meets the strength requirements. The average number of torsion times can reach 11-16 (times), and the average elongation reaches more than 2.5-3.0%.
[0185] The wire drawing speed is 4-4.5m / s, the die temperature during the drawing process is controlled at about 120°C, wire breakage occurs during the drawing process, the strength meets the requirements, the average number of torsion times is less than 10 times, and the average elongation reaches more than 1.5-2.0%.
[0186] After trial production and comparison, it was determined that the drawing speed of the embodiment of the present application was controlled below 3m / s.
[0187] Exemplarily, in the embodiments of the present application, the wire drawing speed (drawing vehicle speed) is 1-3 m / s.
[0188] As an optional example, the above drawing process is carried out using a Mario Frigerio spa / L120 / 9+BU125 / nine-pass continuous high-speed wire drawing machine. The Mario Frigerio spa / L120 / 9+BU125 / nine-pass continuous high-speed wire drawing machine is at the international leading level, with a maximum wire diameter of 16.0mm and a power of 129kW. The general domestic equipment is 90-110kW; it can fully meet the drawing power of 1650MPa ultra-high-strength wire rods and has stability. The production speed can reach a maximum of 7m / s. The equipment uses air cooling and water cooling, and a large wire drawing reel, which can ensure that the steel wire obtains high strength while also meeting the requirements of plasticity and toughness indicators. The production equipment adopts digital intelligent control, with functions such as adjustable tension and arbitrary pass throwing.
[0189] 4. Twisting
[0190] In some embodiments, the mining 2400MPa grade steel strand of the embodiment of the present application is designed into a Westerly structure (1+9+9), and the product structure diagram is as follows: Figure 2 , which is composed of an outer layer of wire 4, an inner layer of wire 5 and a central wire 6. The Siru structure is well known in the art, and the specific structure will not be described in detail here.
[0191] As an optional example, the mining-use 2400 MPa grade steel strand in the embodiment of the present application is a 1×19S-Φ21.8mm Westerly structural steel strand.
[0192] The inventors found that if Figure 3 As shown, the tensile strength of ultra-high-strength steel strand reaches 2400MPa, and it is easy to become loose and cannot be restored by hand.
[0193] The lay pitch design of steel strand has a great influence on the tightness of the steel strand structure. According to the new version of GB / T5224 standard, the lay pitch range of 1×19 structural steel strand is 10-16 times of the nominal diameter of the steel strand. Within this range, multiple process trials were organized and the lay pitch was optimized. Finally, the lay pitch of the steel strand was set to 10-16 times of the nominal diameter of the 1×19S-Φ21.8mm steel strand, preferably 13.5 times. After the stabilization process, the obtained ultra-high-strength steel strand has a tight structure and is not loose. Figure 4 As shown in the photo, it can be seen that the compactness of the 13.5 times lay length design is significantly better than that of the 14.2 times lay length design.
[0194] 5. Stabilization treatment
[0195] Increasing the process temperature of stabilization treatment can make the tempering state of steel strands sufficient. Under the action of appropriate tension, the atoms of high C and high Si elements in the structure can diffuse faster to achieve atomic recombination. Through "pinning", the unstable unbalanced structure is gradually transformed into a stable balanced structure, the internal stress is eliminated, and the plasticity index is improved.
[0196] However, in order to obtain high strength, the process temperature of the stabilization treatment should be increased, and the factors causing large strength loss due to temperature increase should be reduced. Therefore, the process temperature was increased from the original range of 365-385℃ to the range of 390-400℃, and the tempering temperature was divided into 3 groups of 390, 395, and 400℃, and the cross test was carried out with the tension of 40%-50% of the breaking load of the steel strand. At the same time, the speed was reduced from 60m / min for ordinary products to 38-42m / min. The selection of the tension value is inversely proportional to the tempering temperature, ensuring that the diameter of the finished steel strand is reduced by 0.5-0.7% compared with the steel strand after twisting, and obtaining the best tensile strength.
[0197] Therefore, in some embodiments, during the stabilization process, the tension is 310-330 kN, the tempering temperature is 380-400°C, the vehicle speed is 38-42 m / min, and the cooling water temperature is ≥25°C.
[0198] Exemplarily, the cooling water temperature is 25-60°C.
[0199] As a preferred example, during the stabilization treatment, the tension is set to 320 kN, the tempering temperature is 390°C, the vehicle speed is 40 m / min, and the cooling water temperature is 25°C.
[0200] It should be noted that in the embodiments of the present application, the best matching scheme of the process temperature and tension of the stabilization treatment (for example, the above-mentioned preferred scheme) can be obtained through process cross-testing.
[0201] As an optional example, the Mario Frigerio spa / 1×50-1250+MS90 / 12 / 1×7 and 1×19 Xiru and Valinton structural steel strand production lines are used. The stabilization treatment medium-frequency induction furnace is manufactured by the Italian ATE company, with a power of 800kW and a maximum force of 500kN for the tension system. It can provide tension guarantee for the super-large specifications and high-strength prestressed steel strands of 1×7 and 1×19 structures. With the structural design of the steel strand, the structure of the steel strand can be made tight and not loose. The best stabilization treatment process is studied to ensure that the steel strand meets the ultra-high strength performance while maintaining good plasticity indicators.
[0202] In some embodiments, the application of steel strands in coal mines is to make mining anchor cables, which are composed of steel strands, anchoring agents, trays, anchors and other anchoring accessories. Through mechanical tensioning, pressure is applied to the surrounding rock of the mine tunnel for reinforcement, such as Fig. 9 shown.
[0203] The anchor in the anchor cable is a locking device to maintain the preload of the steel strand and transfer it to the rock mass. It needs to be reasonably matched with the steel strand, and the static load anchoring performance test needs to meet the requirements of the MT / T942 "Mining Anchor Cable" industry standard.
[0204] 1×19S- The static load matching test of 2400MPa steel strand and anchor will be affected by the test conditions, which will affect the accuracy of the test results. First of all, the test data of the steel strand body should be accurate. The average value of the maximum force test results is used to calculate the efficiency coefficient of the static load anchoring performance, which is also an evaluation indicator of whether the static load anchoring performance is qualified. On the other hand, the surface hardness of the ultra-high-strength steel strand is increased, and the hardness of the anchor needs to be reasonably matched to obtain a good match during the test, give full play to the overall structural role of the steel strand and anchor, meet the requirements of the test conditions, and avoid problems that affect the test results such as slipping and steel strand shrinkage.
[0205] To this end, the inventors conducted the following research:
[0206] ⑴Use WAW-2000G (200T) tensile testing machine (see Fig.10 ) to conduct tensile tests and solved the technical difficulties in the steel strand testing process.
[0207] In the actual experiment, the following situations were encountered:
[0208] ①The steel strand slips in the tooth plate;
[0209] ② The outer filaments are easily cut inside the tooth plate. (See Fig.11 )
[0210] The above situation caused the test to be invalid or unable to reflect the true performance indicators of the steel strand. Combined with the test anomalies of the ultra-high-strength steel strand, the following improvement measures were taken (see Fig.12 ):
[0211] ① Design and manufacture "extended fine-toothed, densely spaced tooth plates" so that the clamping length of the tooth plates is greater than one lay length of the steel strand;
[0212] ②The tooth pitch was changed from 2.0mm to 1.5mm, and the fine tooth design increased the meshing area between the tooth plate and the specimen;
[0213] ③Use fine sandpaper to protect the sample.
[0214] Through the improvement, the test anomalies such as slipping and scratching of steel strands during the test were effectively solved, which is conducive to the accurate evaluation of ultra-high-strength steel strands.
[0215] ⑵ Designed parameters to match the ultra-high strength steel strand anchor
[0216] The inner hole diameter of the anchor clip and the tapered angle of the clip are designed according to the nominal diameter of the steel strand. After the anchor is assembled, during the stress process, the internal friction angle between the assembled components will reach a balanced state, thereby producing a good anchoring effect. During tunnel support, the steel strand is subjected to vertical stress, especially the ultra-high-strength steel strand. Since its strength and hardness are higher than those of conventional steel strands, it is easy for the steel strand and the anchor clip to be loosely wrapped, misaligned, and the anchor clip to fall off, which affects the anchoring performance. Therefore, during the trial production of the 2400MPa grade steel strand product for mining in the embodiment of the present application, by controlling the product size, designing a small twist pitch, and implementing process measures such as stabilizing the optimal match between temperature and tension, the steel strand structure is made compact and the size homogeneity is good. After testing, the diameter of the product is controlled at 22.14-22.15mm, creating conditions for the successful matching of the anchor.
[0217] ⑶ Matched with ordinary anchors and ultra-high strength anchors respectively, and carried out hardness matching tests. The ultra-high strength anchor was improved in appearance and size and successfully matched. The anchor efficiency coefficient measured by the static load test of the steel strand-anchor assembly was 0.954, and the total elongation of the stressed length of the assembly was 3.2%. The test results fully meet the requirements of the MT / T942 "Mining Anchor Cable" industry standard.
[0218] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0219] Example 1
[0220] The 2400MPa grade steel strand for mining in this embodiment has a Siru structure (such as Figure 2 As shown, it is composed of an outer layer wire 4, an inner layer wire 5 and a center wire 6, and the diameter of the steel strand is 21.8 mm. The manufacturing method of the 2400 MPa grade steel strand for mining comprises the following steps:
[0221] 1. Preparation of Φ14.0mm and Φ8.0mm wire rods
[0222] The method for preparing the wire rod comprises the following steps:
[0223] (1) Design the chemical composition of ingredients
[0224] The ingredients are molten steel in steelmaking, and its chemical composition is: C: 0.938wt%, Si: 1.092wt%, Mn: 0.509wt%, P: 0.012wt%, S: 0.002wt%, Ni: 0.012wt%, Cr: 0.367wt%, Cu: 0.009wt%, V: 0.037wt%, and the balance is Fe.
[0225] The chemical composition of Φ14.0mm and Φ8.0mm wire rods is the same.
[0226] (2) The ingredients of step (1) are subjected to converter, LF refining, RH vacuum degassing, and then rolled into shape by two-fire forming to obtain the wire rod body.
[0227] (3) The wire rod body is subjected to austenitizing heating and isothermal salt bath sorbitizing treatment to obtain the wire rod.
[0228] in:
[0229] The method of austenitizing heating is: using an offline salt bath process, the wire rod is re-laid out, the coiled wire rod is straightened and then enters a heating furnace for austenitizing heating. The austenitizing heating temperature is 930°C. After keeping warm for 10 minutes, it is transferred to a cooling salt bath furnace.
[0230] The method of isothermal salt bath troostitizing treatment is as follows: the wire rod entering the cooling salt bath furnace is subjected to isothermal heat treatment in a salt bath at 500°C, and the wire rod undergoes isothermal troostite phase transformation in a fine and uniform austenite structure. The salt bath adopts a molten state of a mixed salt of nitrite, which is composed of 50wt% sodium nitrite and 50wt% potassium nitrite; the single wire salt bath treatment time is 2 minutes.
[0231] ① The chemical composition of the wire rod obtained in step (3) (i.e., the salt bath wire rod) was detected using SPECTROLAB spectroscopy. The test results are shown in Table 2.
[0232] Table 2 Chemical composition of salt bath wire rod in Example 1
[0233]
[0234] ② The wire rod obtained in step (3) (i.e., salt bath wire rod) was subjected to high-magnification tissue examination using a German Zeiss Axio optical microscope. The results are shown in Table 3.
[0235] Table 3 Metallographic structure test results of salt bath wire rod of Example 1
[0236] Inclusion level A: / B: / C: / D:0.5 DS: / organize 97% Sostenite + 3% (Pearlite + Ferrite) Decarburization layer depth 0.05mm, 0.35%D
[0237] Figure 5 This is a metallographic photograph of the wire rod obtained by isothermal salt bath sorbitization treatment in Example 1. Figure 5 It can be seen that the troostitization rate of the wire rod reaches 97%, and the network carbides and other structures that affect drawing are eliminated, and the microstructure is more uniform and refined.
[0238] ③ The mechanical properties of the wire rod obtained in step (3) (i.e., salt bath wire rod) are shown in Table 4.
[0239] Table 4 Mechanical properties of salt bath wire rod raw materials in Example 1
[0240]
[0241] Note: Except for the test data in the last row in Table 4, the rest of the rows are the data of five actual measurements of Φ14.00mm salt bath wire rod. It is normal for the actual measured wire rod values to differ, as long as the deviation range is maintained.
[0242] The test results of Tables 2 to 4 show that, through the scheme of the present application, the diameter allowable deviation of the wire rod is controlled within ±0.20mm, and the ovality is ≤0.15mm, which is stricter than the dimensional control level of ordinary wire rods (the diameter allowable deviation is ±0.30mm, and the ovality is ≤0.48mm). The initial strength average of the Φ14.00mm wire rod reaches more than 1620MPa; the initial strength of the Φ8.00mm wire rod reaches 1572MPa; the strength standard deviation does not exceed ±5MPa, and the surface shrinkage rate reaches more than 30%.
[0243] The obtained wire rod dimensional accuracy, organizational state and mechanical properties all meet the design requirements. While achieving high strength, the wire rod has excellent mechanical properties, solving the problem of poor plastic toughness index of the wire rod after high C and high Si strengthening treatment, which causes the subsequent wire drawing process to break and unable to produce normally. It also realizes the aging-free treatment, and users can put it into use directly. In comparison, the aging period of ordinary wire rods is 20 days, and the aging period of winter wire rods is 30 days. Therefore, the capital occupation time of using this wire rod can be shortened by at least 30 days.
[0244] 2. Manufacturing process of steel strand
[0245] The Φ14.00mm wire rod and the Φ8.00mm wire rod obtained in step 1 are subjected to surface treatment processes of pickling and phosphating, and are then drawn, twisted and stabilized, and then layer-wound to obtain ultra-high-strength steel strands.
[0246] ⑴ Pickling and phosphating surface treatment process (such as Figure 1 (shown)
[0247] Wire rod threading: The ground loading vehicle delivers the raw wire rod to be used to a hanging moving device (e.g., a crane), which places the raw wire rod in the pickling process implementation position.
[0248] ①The pickling process includes diving pickling, first pickling, second pickling, third pickling, fourth pickling, fifth pickling, immersion and first rinsing process. Among them:
[0249] The method of submersible washing is: soak the raw material wire rod in a submersible pool filled with tap water for 2 hours. The submersible pool has a heating coil.
[0250] The methods of the first pickling, the second pickling, the third pickling, the fourth pickling and the fifth pickling are all: soaking the raw wire rod washed by submersible washing in new hydrochloric acid.
[0251] The rinsing method is: use tap water to wash away the hydrochloric acid on the surface of the raw wire rod after the first to fifth pickling treatments.
[0252] The first flushing method is: use a high-pressure water gun with a pressure of 0.5MPa to flush the soaked raw material wire rod, and a 15kW centrifugal pump is configured in the first flushing process.
[0253] The temperature of the submersible pool used for submersible washing is preheated, and the bath liquid can also reach the process requirements of normal temperature (25°C) in winter, which can ensure the process temperature of the ultra-high strength ring diameter wire rod washing line. The hydrochloric acid concentrations of the pickling tanks corresponding to the first pickling, the second pickling, the third pickling, the fourth pickling, and the fifth pickling are respectively controlled to be: 9.5wt%, 15wt%, 16wt%, 17.5wt%, 17.5wt%, and the time used for the first pickling, the second pickling, the third pickling, the fourth pickling, and the fifth pickling is 4min, 4min, 4min, 4min, and 4min. The total time of each pickling is 20min, the immersion time is 13s, and the flushing time is 1min.
[0254] ②The phosphating process includes the first warm washing, phosphating, the second rinsing, the second warm washing, saponification, and drying process. Among them:
[0255] The first warm washing method is: use 30°C hot water to wash the raw material wire rod after the first rinse.
[0256] The phosphating method is: immersing the raw wire rod after the first warm wash in phosphoric acid for phosphating treatment.
[0257] The second flushing method is: use a high-pressure water gun with a pressure of 0.5MPa to flush the phosphating wire rod, and a 15kW centrifugal pump is configured for the second flushing process.
[0258] The second warm washing method is: use 30°C hot water to wash the phosphating wire rod after the second rinse.
[0259] The saponification method is as follows: the phosphated wire rod after the second rinse is saponified in a sodium stearate aqueous solution at 80° C. for 45 seconds, and the pH value of the saponification tank is 7-8.
[0260] During the phosphating process, the total acidity (point) was 100, the free acidity (point) was 13.5, the acid ratio was 6.5, and the phosphating time was 5 minutes.
[0261] After the phosphating process, the hanging mobile device puts the surface treated wire rod into the ground loading car, and the wire rod is unloaded.
[0262] After testing, the thickness of the phosphating film after treatment reached 10g / m 2 (The thickness of the conventional product phosphate film is 6.0-7.0g / m 2), and the phosphating film is uniform and dense, and can withstand temperatures of 400 to 500°C, which effectively solves the wear of the die during ultra-high strength wire rod drawing, improves the surface quality of the steel wire, and is also beneficial to the improvement of the corrosion resistance and stress corrosion resistance of the finished steel strand.
[0263] ⑵Drawing process
[0264] ① Design the wire drawing die. Use a small-angle working cone and a short sizing belt design. The working cone of the first two dies is designed to be 12°; the working cone angle of the last two dies is designed to be 8°, and the sizing belt is controlled at 0.2d.
[0265] ②Design wire drawing process.
[0266] The inner wire semi-finished product is drawn from 8mm to 3.15mm, with a compression rate of 84.49%, using a 9-pass drawing process:
[0267] 8.00→7.20→6.40→5.70→5.09→4.56→4.12→3.75→3.42→3.18;
[0268] The outer layer wire semi-finished product is drawn from 14.0mm to 5.55mm, with a compression rate of 84.28%, using a 9-pass drawing process:
[0269] 14.00→12.80→11.52→10.25→9.15→8.19→7.38→6.68→6.07→5.55;
[0270] The center wire semi-finished product is drawn from 14.0mm to 6.25mm, with a compression rate of 80.07%, using an 8-pass drawing process:
[0271] 14.00→12.80→11.52→10.25→9.15→8.19→7.38→6.68→6.25.
[0272] ③ Use Mario Frigerio spa / L120 / 9+BU125 / 9-pass continuous high-speed wire drawing machine for production. The wire drawing speed is controlled at 3m / s. Use a temperature gun to monitor the process temperature of each pass out of the mold. It is required to replace the mold and replenish the lubricating powder before starting. Check whether the cooling water pipeline is operating normally. According to the regulations, the lubricating powder must not be less than 1 / 2 of the mold box height. By implementing control over each link such as drawing lubrication and drawing cooling, it is ensured that the process temperature of the last pass of the wire out of the mold is controlled below 100°C (the process requirement value is not higher than 120°C). The entire drawing process is monitored, and there is no wire breakage. The surface quality of the Φ5.55 semi-finished steel wire obtained is good, without cracks, and there is a good plastic fracture at the break (see Figure 7), the average tensile strength reached 2486.45MPa, and the elongation reached more than 2.5%. The semi-finished product test data of the outer layer wire, inner layer wire and center wire are shown in Table 5.
[0273] Table 5 Wire drawing process and semi-finished product performance of Example 1
[0274]
[0275]
[0276] It can be seen that the tensile strength of the semi-finished product drawn by the wire rod prepared in this embodiment reaches more than 2400 MPa, and the elongation reaches more than 2.5%, which can meet the process design requirements.
[0277] ⑷ Twisting and stabilization process
[0278] ① Use Mario Frigerio spa / 1×50-1250+MS90 / 12 / 1×7 and 1×19 Xiru and Warinton structural steel strand production lines for twisting and stabilization treatment to obtain.
[0279] The specific operations of twisting and stabilization are well known in the industry.
[0280] ② The lay length of the designed steel strand is 2400MPa grade 1×19S- 13.5 times the nominal diameter of the steel strand.
[0281] ③ The process parameters of stabilization treatment are set as follows: tension is 320kN (42.67% of the designed breaking load of the steel strand), tempering temperature is 390℃, vehicle speed is 40m / min, and cooling water temperature is 25℃.
[0282] After testing, the elongation of the stabilized steel strand is ≥6.5%, and the tensile strength of the steel strand reaches the design requirement of 2400MPa. The steel strand obtained by the tensile test has a normal plastic fracture. Figure 8 .
[0283] (4) Layer winding
[0284] The twisted and stabilized steel strands are wound in layers to obtain the 2400 MPa grade steel strands for mining in this embodiment.
[0285] The layer winding method is: use a layer winding machine to layer-wind the twisted and stabilized steel strands, and try to ensure that the outermost layer of the steel strands is full. After the steel strands are layered, samples are taken for testing. Eight steel strips are evenly tied axially for each coil of steel strands, and one steel strip can be tied circumferentially, and the circumferential direction must be perpendicular to the axial steel strip at 90°.
[0286] The samples were sent to a third-party testing center designated by the state for testing (testing was based on GB / T5224-2023 "Steel Strand for Prestressed Concrete"). The steel strand structure was tight, the diameter of the steel strand was controlled at 22.14-22.15mm, the maximum force reached more than 750kN, the tensile strength reached 2400MPa, the elongation index reached more than 6.5%, and the steel strand had a normal plastic fracture. The design indicators of the steel strand have been achieved, and the test results are shown in Table 6.
[0287] Table 6 Outsourcing test data of finished steel strands in Example 1
[0288]
[0289]
[0290] Note: After layer winding, the stranded steel wire becomes small coils. B24022049-1, B24022049-2, and B24022049-3 refer to the numbers of 3 coils.
[0291] The 2400MPa grade steel strand for mining manufactured in this embodiment is assembled with a 1860MPa anchor produced by a first manufacturer (referred to as anchor 1#), a 1860MPa anchor produced by a second manufacturer (referred to as anchor 2#), and a 2230MPa anchor produced by a third manufacturer (referred to as anchor 3#). Fig. 9 The mining anchor cable (i.e., steel strand-anchor assembly) shown is subjected to a static load performance test, and the static load performance test method is MT / T942 "Mining Anchor Cable".
[0292] The static load performance test results are shown in Table 7.
[0293] Table 7 Static load test data of steel strand-anchor assembly
[0294]
[0295] As can be seen from Table 7, the 2400MPa grade steel strand products for mining manufactured in this embodiment were matched with ordinary anchors (anchor 1# and anchor 2#) and ultra-high strength anchors (anchor 3#), respectively. The matching effect with ordinary anchors was poor and did not meet the standard requirements. The ultra-high strength anchors were successfully matched, and the anchor efficiency coefficient measured by the static load test of the steel strand-anchor assembly was 0.954, and the total elongation of the force-bearing length was 3.2%, which met the MT / T942 "Mining Anchor Cable" standard requirements.
[0296] Example 2 (Compared with Example 1, the wire rod ingredients and the salt bath wire rod composition are different)
[0297] This embodiment is basically the same as Embodiment 1, except that:
[0298] In the method for preparing the wire rod:
[0299] In step (1):
[0300] The ingredients are molten steel in steelmaking, and its chemical composition is: C: 0.954wt%, Si: 1.097wt%, Mn: 0.509wt%, P: 0.011wt%, S: 0.002wt%, Ni: 0.009wt%, Cr: 0.353wt%, Cu: 0.008wt%, V: 0.034wt%, and the balance is Fe.
[0301] In step (3):
[0302] ① Use SPECTROLAB spectroscopy to detect the chemical composition of the wire rod obtained in step (3) (i.e., salt bath wire rod). The test results are shown in Table 7.
[0303] Table 7 Chemical composition of salt bath wire rod in Example 2
[0304]
[0305] ② Use a German Zeiss Axio optical microscope to perform high-magnification tissue examination on the wire rod obtained in step (3) (i.e., salt bath wire rod). The results are shown in Table 8.
[0306] Table 8 Metallographic structure test results of salt bath wire rod of Example 2
[0307] Inclusion level A:0.5B: / C: / D:0.5DS: / Organization 96% Sostenite + 4% (Pearlite + Ferrite) Decarburization layer depth 0.06mm, 0.428%D
[0308] Comparative Example 1 (Compared with Example 1, excluding isothermal salt bath troostitization treatment)
[0309] This comparative example is basically the same as Example 1, except that:
[0310] In the method for preparing the wire rod, in step (3), the wire rod body is subjected to austenitizing heating but no isothermal salt bath troostitizing treatment is performed.
[0311] Figure 6 This is a metallographic photograph of the wire rod of Comparative Example 1, Φ14.00 mm, obtained without isothermal salt bath sorbitization treatment. Figure 6 It can be seen that its grain size is obviously coarse, the uniformity is poor, the interlamellar spacing is large, and the troostitization rate is low.
[0312] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0313] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0314] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A wire rod, characterized in that: The chemical composition of the wire rod is calculated by mass percentage: C: 0.92-0.97%, Si: 1.00-1.10%, Mn: 0.50-0.60%, P≤0.015%, S≤0.015%, Cu≤0.10%, Ni≤0.015%, Cr≤0.40%, V≤0.1%, and the balance is Fe.
2. The wire rod according to claim 1, characterized in that The metallographic structure of the wire rod is troostite, and the troostitization rate is above 95%.
3. The wire rod according to claim 1, characterized in that The diameter of the wire rod includes 14.0 mm and 8.0 mm, and the allowable deviation range is ±0.20 mm, and the ovality is less than 0.15 mm; and / or, The initial strength of the wire rod is 1510-1650 MPa, and the cross-sectional shrinkage is above 30%; and / or, The coil diameter of each coil of the wire rod is 1.35-1.4m.
4. A method for preparing a wire rod according to any one of claims 1 to 3, characterized in that: include: Design the chemical composition of ingredients; The ingredients are subjected to converter, LF refining, RH vacuum degassing, and then rolled into shape by two-fire forming to obtain the wire rod body; The wire rod body is subjected to austenitizing heating and isothermal salt bath sorbitizing treatment to obtain the wire rod.
5. The preparation method according to claim 4, characterized in that: The chemical composition of the ingredients is calculated by mass percentage: C: 0.92-0.97%, Si: 1.00-1.10%, Mn: 0.50-0.60%, P≤0.015%, S≤0.015%, Cu≤0.10%, Ni≤0.015%, Cr≤0.40%, V≤0.1%, and the balance is Fe; and / or, The rolling is carried out by using the Morgan seventh generation 8+4 rolling mill; and / or, During the rolling process, a φ250 mm round billet is used to roll a φ14.0 mm wire rod body, and the compression ratio is 318.9%.
6. A 2400MPa grade steel strand for mining, characterized in that: Made from the wire rod according to any one of claims 1 to 3 or the wire rod prepared by the preparation method according to claim 4 or 5; Preferably, the diameter of the 2400MPa grade steel strand for mining is 21.8mm; and / or, the 2400MPa grade steel strand for mining has a Siru structure; and / or, the tensile strength of the 2400MPa grade steel strand for mining is 2400-2600MPa, the elongation is greater than 6%, and the maximum force is 750-814kN.
7. A method for manufacturing a 2400MPa grade steel strand for mining as claimed in claim 6, characterized in that: include: The wire rod is subjected to a surface treatment of pickling and phosphating to obtain a surface-treated wire rod; The surface treated wire rod is subjected to wire drawing, twisting, stabilization treatment and layer winding to obtain the mining-use 2400MPa grade steel strand.
8. The manufacturing method according to claim 7, characterized in that: The surface treatment includes wire rod threading, submersible washing, at least one of the pickling, immersion, first rinsing, first warm washing, phosphating, second rinsing, second warm washing, saponification, drying and wire rod offline; and / or, The total acidity of the phosphating is 85-105, the free acidity is 12-15, the acid ratio is 5-8, and the phosphating time is 4-6 minutes; and / or, In the wire drawing process, both the outer layer wire semi-finished product and the inner layer wire semi-finished product are drawn in 9 passes, the working cone angle of the first two passes of the die is 11-12°, the working cone angle of the last two passes of the die is 7-8°, and the sizing zone is 0.2d; and / or, During the wire drawing process, the outer layer of the semi-finished wire is drawn from 14.0 mm to 5.55 mm, with a compression rate of 84.28%; and / or, In the wire drawing process, the inner layer wire semi-finished product is drawn from 8 mm to 3.15 mm, with a compression rate of 84.49%; and / or, During the wire drawing process, the center wire semi-finished product is drawn from 14.0 mm to 6.25 mm, the compression rate is 80.07%, and an 8-pass drawing process is adopted; and / or, The wire drawing speed is set at less than 3 m / s; and / or, The twisting pitch setting value is 10-16 times the nominal diameter of the 1×19S-Φ21.8mm steel strand; During the stabilization treatment, the tension is 310-330 kN, the tempering temperature is 380-400° C., the vehicle speed is 38-42 m / min, and the cooling water temperature is 25-60° C.; and / or, The method for manufacturing the 2400MPa grade steel strand for mining further comprises the step of designing the structure of the steel strand to be a Westerly structure.
9. The manufacturing method according to claim 8, characterized in that: The submersible pool used for the submersible washing is provided with an oil heating system for preheating the submersible pool; and / or, The pickling, leaching and phosphating are all carried out under the condition of intermittent air blowing and stirring; and / or, The number of pickling is 5 times, and the concentration of the acid used in each pickling is 5-14wt%, 10-20wt%, 12-20wt%, 14-21wt%, and 14-21wt% respectively according to the number of pickling from the beginning to the end; and / or, The total pickling time is 18-22 minutes; and / or, And / or, the immersion time is 12-15s; and / or, The duration of the first flushing and the second flushing is 1-2 minutes; and / or, The allowable deviations of the diameters of the outer layer wire semi-finished product, the inner layer wire semi-finished product and the center wire semi-finished product are all within a range of -0.01 mm to +0.02 mm.
10. A mining anchor cable, characterized in that: It includes the 2400MPa grade steel strand for mining as described in claim 6 or the 2400MPa grade steel strand for mining manufactured by the manufacturing method as described in any one of claims 7 to 9.
Citation Information
Cited By
Hot-rolled wire rod for 2460MPa-grade stranded wire and manufacturing method of hot-rolled wire rod
CN121976125A
High-strength complex-phase hot-rolled wire rod for 2460MPa-grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN122013052A
High-strength complex-phase hot-rolled wire rod for 2460mpa grade strand and manufacturing method thereof
CN122013052B
A multi-pass small deformation drawing process for making high strength steel wire
CN122722682A